Prediction study and in vitro safety profile of bioactive molecules derived from Euterpe oleracea Mart. extract - Ribeiro, Luana Coden; Davidson, Carolina Bordin; Montagner, Taíse Regina Schuster; Bonazza, Giovana Kolinski Cossettin; de Souza, Diulie Valente; Machado, Alencar Kolinski (Disciplinarum Scientia | Saúde, 2026)
Natural products have been highlighted for their bioactive properties. Euterpe oleracea Mart. (açaí) is a fruit that has been extensively investigated due to its significant effects on human health. However, due to the heterogeneous chemical matrix of açaí, its biological effects may be attributed to the bioactive molecules present in the extract. The objective of this study was to evaluate the biological properties of the 5 more abundant molecules of açaí extract, developing a study of prediction. Also, it was analyzed the catechin, apigenin and epicatechin in vitro safety profile. The prediction study was performed using the PASS online tool. The in vitro safety profile was conducted by using BV-2 cell line in different periods of incubation. The obtained results shown that catechin, epicatechin, epigallocatechin, apigenin and taxifolin were the most important elements at açaí’s chemical matrix. These molecules were capable to positively modulate different parameters related to the oxidative metabolism and inflammatory pathways. Finally, most of the tested bioactive molecule’s concentrations presented satisfactory in vitro safety profile. The results suggest that the known effects of the extract may occur as a result of the most abundant molecules in the chemical matrix of this natural product.